Implementing Learning Strategies in Vocabulary Acquisition of Good Bilingual EFL Student in Indonesia Contexts: A Study of Good Bilingual EFL Senior High School Student - rigel sampelolo (Teaching English as a Foreign Language Overseas Journal, 2017)
The study was based on some of the findings of a fieldwork conducted in 2017, This study intended to find out the comprehensive description about learning strategies implemented bythe good Bilingual EFL student in acquiring vocabulary. The method used in this research was qualitative descriptive method. Data were generated by classroom observations in senior high school and by indepth interviews with the student, friends and teachers. Based on the main findings of this research, Implications were discussed of the student’s strategies.